Diagnosis and Management of Lynch Syndrome - C. da Silva, Felipe; D. Valentin, Mev; M.M. Santos, Erika; O. Ferreira, Fabio; Aguiar, Samuel; I. Palmero, Edenir; M. Rossi, Benedito (Recent Patents on Regenerative Medicine, 2011)
Lynch syndrome (LS), or hereditary nonpolyposis colorectal cancer (HNPCC), represents 2% - 4% of all cases of colorectal cancer. LS is an autosomal-dominant inherited cancer predisposition syndrome caused by germline mutations in deoxyribonucleic acid (DNA) mismatch repair genes. Since the discovery of the major human genes with DNA mismatch repair function, mutations in five of them have been correlated with susceptibility to LS: mutS homolog 2 (MSH2); mutL homolog 1 (MLH1); mutS homolog 6 (MSH6); postmeiotic segregation increased 2 (PMS2); and postmeiotic segregation increased 1 (PMS1). The diagnostic features of LS have accumulated and been refined over time. Today, LS is defined by a set of clinical, pathological, and molecular features that encompass: a family history of colorectal cancer, a particular spectrum of extracolonic neoplasms, multiple colorectal tumors, early onset of cancer, particular histological features among colorectal cancers, presence of DNA microsatellite instability, loss of expression of DNA mismatch repair proteins, and germline mutation in a DNA mismatch repair gene. This review provides an overview of the diagnosis and management of LS patients, including some recently reported patents.
Keywords: Oxaliplatin